Modulation of immune responses using adjuvants to facilitate therapeutic vaccination - Lavelle, Edward (My University, 2020)
Therapeutic vaccination offers great promise as an intervention for a diversity of infectious and non-infectious conditions. Given that most chronic health conditions are thought to have an immune component, vaccination can at least in principle be proposed as a therapeutic strategy. Understanding the nature of protective immunity is of vital importance, and the progress made in recent years in defining the nature of pathological and protective immunity for a range of diseases has provided an impetus to devise strategies to promote such responses in a targeted manner. However, in many cases, limited progress has been made in clinical adoption of such approaches. This in part results from a lack of safe and effective vaccine adjuvants that can be used to promote protective immunity and/or reduce deleterious immune responses. Although somewhat simplistic, it is possible to divide therapeutic vaccine approaches into those targeting conditions where antibody responses can mediate protection and those where the principal focus is the promotion of effector and memory cellular immunity or the reduction of damaging cellular immune responses as in the case of autoimmune diseases. Clearly, in all cases of antigen-specific immunotherapy, the identification of protective antigens is a vital first step. There are many challenges to developing therapeutic vaccines beyond those associated with prophylactic diseases including the ongoing immune responses in patients, patient heterogeneity, and diversity in the type and stage of disease. If reproducible biomarkers can be defined, these could allow earlier diagnosis and intervention and likely increase therapeutic vaccine efficacy. Current immunomodulatory approaches related to adoptive cell transfers or passive antibody therapy are showing great promise, but these are outside the scope of this review which will focus on the potential for adjuvanted therapeutic active vaccination strategies
PUBLISHED
Keywords: immunomodulatory; autoimmune diseases; infectious and non-infectious conditions; Adjuvant; Autoimmunity; Cancer; Cellular immunity; Therapeutic; Vaccine; Cancer; Immunology, Inflammation & Infection